The readiness of geography teachers to use mobile devices in the context of immersive technologies integration into the teaching process - Stojšić, Ivan; Ivkov-Džigurski, Anđelija; Maričić, Olja (Geographica Pannonica, 2019)
The rapid development of immersive technologies has opened up the possibilities for using augmented, mixed, and virtual reality in education. The theoretical part of this paper included literature review of previous studies dealing with the use of augmented and virtual reality in geography teaching and learning. However, a question raised regarding the readiness of geography teachers to integrate mobile devices and use the advantages of immersive technologies in practice. Based on their digital competences and readiness to use mobile devices and other information and communication technologies in the teaching process four groups of geography teachers can be separated using cluster analysis. The clusters are: 1) Confident and innovative, 2) Traditional approach, 3) Optimistic but low-digitally skilled, and 4) Pessimistic but digitally skilled teachers. Teachers (particularly those in the first cluster) highly assessed the possibilities of using immersive technologies in practice (especially with the physical and regional geography teaching contents).
Keywords: augmented reality; educational technology; geography teacher; geography teaching; immersive teaching; mobile learning; virtual reality